Empirical Evidences of Romanian Auditors' Behavior Regarding Creative Accounting Practices - Diana Elisabeta Balaciu; Victoria Bogdan; Ioana Teodora Mester; Dana Gherai (Journal of Accounting and Management Information Systems (JAMIS), 2012)
A highly qualitative financial reporting refers to the publication of accounting information complying with the requirements of the reporting framework and generally, they must be transparent, intelligible, relevant, credible and comparable. Based on the results of the theoretical research regarding the auditors' behavior regarding creative accounting practices, this paper investigates Romanian auditors' attitude. To this purpose we set up an empirical study that has as main objective the identification of the financial auditors' perception regarding the existence and the forms of manifestation of the creative accounting phenomenon in the companies which made the object of our study. After analyzing the results of the information provided by descriptive statistics, we can conclude that all of the creative accounting practices mentioned in survey had been encountered quite frequently by the auditors in our sample, the lowest incidence being the one that regarded the creative accounting practices affecting the financial assets. Only a few studies in the Romanian accounting literature are focused upon investigating or exploring different empirical evidences of Romanian auditors' behavior regarding creative accounting practices. Our study contributes to the existing accounting literature on the topic by testing research propositions referring to the auditors' perception of the users' interests and the existence and frequency of creative accounting practices.
Keywords: M41; M42; 650; creative accounting; auditors; behavior; manipulation; Romanian companies